Hepatitis B screening before rituximab therapy: a multicentre South Australian study of adherence. Issue 8 (7th August 2018) - Hall, Samuel A. L.; Shaikh, Abdul; Teh, Kailin; Tantiongco, Mahsa; Coghlan, Douglas; Karapetis, Chris S.; Chinnaratha, Mohammad A.; Woodman, Richard; Muller, Kate R.; Wigg, Alan J.
Abstract: Background: International guidelines recommend screening for hepatitis B virus (HBV) infection prior to administration of rituximab, due to high risk of HBV reactivation in at‐risk patients. Aims: To determine: (i) adherence to the South Australian (SA) protocol for HBV screening; (ii) HBV prevalence in patients receiving rituximab; and (iii) outcomes of patients at risk of HBV reactivation. Methods: All patients commenced on rituximab at the six major SA public hospitals during a 12‐month period were included in the study. Adherence was assessed by documentation of both hepatitis B surface antigen (HBsAg) and hepatitis B core antibody (HBcAb) prior to initiation of rituximab. Patients were observed for a minimum of 6 months following rituximab initiation. Results: Four hundred and thirty eight patients were included in the study. The main indication for rituximab therapy was haematological malignancy (76.0%). Two hundred and nine (47.7%) failed to receive appropriate HBV screening, 86 (19.6%) had neither HBsAg nor HBcAb performed, and 119 (27.2%) had only HBsAg performed. The identified prevalence of at‐risk cases (either HBsAg‐ or HBcAb‐positive) within the study population was 4.6% (20/438 cases). One case of HBV reactivation was identified, but none led to acute liver failure, transplantation or death. Conclusions: Poor adherence to HBV screening protocols suggests the need for targeted clinician education and system redesign. While the rate of reactivation was low, the prevalence of at‐risk patients in this population was high and justifies further initiatives to increase adherence rates to HBV screening pre‐rituximab.